Rabbit semen metabolism - Abdel-Ghaffar A.E.; El Azab A.I.; El Dawy K.H. (Rabbit production in hot climates, 1994)
The present investigation aimed to assess the sperm metabolism in rabbits. Six mature NZW bucks were used. Ejaculates were extended in sodium citrate buffer and incubated at 37 degrees Celsius for 3 hours. Significant decrease in the number of motile and viable sperm cells was noticed with the advancement of incubation. The time required for reduction of methylene blue was prolongued during the second and third hours of incubation. The lactate dehydrogenase (LDH) activity was significantly higher in the second than in the first ejaculate. LDH activity was significantly increased during the first hour followed by a gradual decrease with the advancement of incubation. The rate of fructose utilization was greatly affected by the period of incubation and sequence of ejaculation. It decreased during the second and third hours of incubation and in the first ejaculate. The correlation coefficients between some of the parameters studied were also calculated.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)